Assessment of early dental arch growth modification with removable maxillary expansion by cone-beam computed tomography and lateral cephalometric radiographs: a retrospective study - Yun Zhang; Jing Yang; Xiaobing Li (BMC, 2023)
Abstract Background This study evaluated the skeletal and dental changes of patients brought by early removable maxillary expansion (ERME) treatment to explore the clinical treatment effect of ERME on early dental arch growth modification. Methods Subject children aged 6-10 years with a maxillary transverse deficiency received ERME treatment, cone-beam computed tomography (CBCT) and lateral cephalometric radiographs were measured before and after treatment, and statistical differences in the measured items were evaluated with corresponding statistical methods to explore the skeletal and dental changes. Results After ERME treatment, there was a statistical increase in the maxillary basal bone arch width, nasal cavity width, maxillary alveolar bone arch width, and maxillary dental arch width. A buccal inclination of the maxillary alveolar bone and a buccal inclination and buccal movement in the alveolar bone of maxillary first molars were found. The maxillary skeletal expansion was statistically greater than the dental expansion. Increases in the mandibular alveolar bone arch width and dental arch width happened after treatment. A decrease in angle ANB and an increase in Ptm-A, U1-SN, U1-PP, L1-MP, and L6-MP were found after treatment. No statistical changes in the growth pattern-related measured items were observed. Conclusions ERME could expand the maxillary basal bone arch width, nasal cavity width, maxillary alveolar bone arch width, and maxillary dental arch width. The maxillary skeletal expansion was greater than the dental expansion. Secondary increases in the mandibular alveolar bone and dental arch widths would happen after ERME. ERME would result in a mandibular advancement, a labial inclination of maxillary anterior teeth, and an increase of maxillary sagittal length, and would not change the patient's growth pattern. Trial registration This study was approved by the Institutional Review Board of the West China Hospital of Stomatology, Sichuan University. (WCHSIRB-D-2020-446).